Odpowiedzialność społeczna jako kategoria współczesnej teorii... - Niemiec, Barbara (Horyzonty Wychowania, 2017)
The article presents the analysis of the concept of responsibilityon the basis of contemporary philosophical thought,showing, at the same time, its pedagogical implications. It constitutedthe starting point for defining the notion of social responsibilityas a kind of relation linking the doer with his deed, beingthe answer to some value and/or its consequences and revealingthe following features:– the doer is collective entity,– the doer is an individual but his deed and/or its consequencesrefer to the social addressee,– the subject of responsibility is another man, community,common good; one can also refer to social responsibility inthe case its subject is the doer or his personal property for thesake of social consequences of the deed,– the instance imposing responsibility is community, articulatedthrough the accepted system and hierarchy of values, currentnorms, customs, models of roles and holding dignity,– the executor is community equipped with sanctions in the formof informal rewards and punishments.The article expresses the reflection upon the need and possibilitiesof shaping the above-defined social responsibility in thelight of contemporary tendencies in theory and practice in educationas well as the context of social life.